2019
DOI: 10.1021/acs.biochem.9b00574
|View full text |Cite
|
Sign up to set email alerts
|

Replication of the Enzymatic Temperature Dependency of the Primary Hydride Kinetic Isotope Effects in Solution: Caused by the Protein-Controlled Rigidity of the Donor–Acceptor Centers?

Abstract: The change from the temperature independence of the primary (1°) H/D kinetic isotope effects (KIEs) in wild-type enzyme-catalyzed H-transfer reactions (ΔE a = E aD – E aH ∼ 0) to a strong temperature dependence with the mutated enzymes (ΔE a ≫ 0) has recently been frequently observed. This has prompted some enzymologists to develop new H-tunneling models to correlate ΔE a with the donor–acceptor distance (DAD) at the tunneling-ready state (TRS) as well as the protein thermal motions/dynamics that sample the sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(80 citation statements)
references
References 82 publications
6
74
0
Order By: Relevance
“…The KIE's were calculated using the second-order rate constants (k's). The measurements of the kinetics of the reactions of the two isotopologues for KIE derivation (= kH/kD) were done on the same day (back to back) using the same batch of distilled acetonitrile solvent (6 kinetic runs each) and were repeated on different days for the temperature range of 40 ℃ 1,11. We also often used different batches of substrates in the determination of the KIE's in order to test the effect of possible different impurity on the KIE measurements, and we did not find apparent differences.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The KIE's were calculated using the second-order rate constants (k's). The measurements of the kinetics of the reactions of the two isotopologues for KIE derivation (= kH/kD) were done on the same day (back to back) using the same batch of distilled acetonitrile solvent (6 kinetic runs each) and were repeated on different days for the temperature range of 40 ℃ 1,11. We also often used different batches of substrates in the determination of the KIE's in order to test the effect of possible different impurity on the KIE measurements, and we did not find apparent differences.…”
mentioning
confidence: 99%
“…The link of DAD TRS distributions to Δ E a ’s has prompted us to start a new research direction to study the structure−Δ E a relationship for the H-transfer reactions in solution . Understanding of this relationship could not only provide insight into the above explanations for the observed trends of Δ E a ’s in enzymes but also help find the appropriate models for H-transfer chemistry.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have found that within the limits of the experimental error, wild-type enzymes show temperature-independent KIEs on the hydride transfer. 9 , 34 , 113 , 114 The behavior is generally explained by precise positioning of the substrate in the ground-state complex, leading to a narrow distribution of DADs at the tunneling-ready state of a well-preorganized protein conformation. 13 , 85 A change in temperature will not cause a DAD population shift, and since both isotopes are affected similarly, the KIE change with temperature will be minimal.…”
Section: Discussionmentioning
confidence: 99%